On the notion of «expertise» in the investigation of environmental crimes (Journal of actual problems of jurisprudence, 2019)
The article discusses the concept and meaning of «expertise» in investigating environmental crimes. Showing the views of various authors made a comparative analysis of the term «specialized knowledge» and «special knowledge» of new and old criminal procedure legislation of the Republic of Kazakhstan. Author examined peculiarities of application of special knowledge in forensic environmental expertise in investigating environmental crimes.Key words: Special knowledge, environmental crime, criminal offense, special knowledge, skills, specialist expertise, research, forensic environmental expertise.